Development of an energy-efficient expander-compressor unit for refrigeration systems - Yap, Ken Shaun (2017)
The thesis presents the development of a novel expander-compressor unit, named cross vane expander-compressor, or in short CVEC. This device is conceived with the primary motivation of integrating the function of the expander and compressor into a single simple geometry, making energy recovery and efficiency improvement economically practical.